Communication Strategies of Islamic Religious Counselors in Realizing Sakinah, Mawaddah, and Warahmah Families in Siempat Nempu Sub-district, Dairi Regency - Manik, Heri I Gajah; Muktarruddin, Muktarruddin (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to explore the communication strategies used by Islamic Religious Counselors in realizing sakinah, mawaddah, and warahmah families in Siempat Nempu Sub-district, Dairi Regency. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews with religious counselors, participatory observations, and analysis of related documents. The findings indicate that effective communication strategies include using language that is easily understood by the community, personal and familial approaches, and utilizing local media such as community radio and WhatsApp groups. Counselors also apply participatory methods by involving the community in discussions and religious activities. Supporting factors such as support from community leaders and cooperation with local government institutions also play a significant role in the success of these communication strategies. Thus, appropriate communication strategies can help in achieving harmonious and prosperous families in accordance with the principles of sakinah, mawaddah, and warahmah.